2020
DOI: 10.3389/fonc.2020.562558
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax-Based Combinations in Acute Myeloid Leukemia: Current Evidence and Future Directions

Abstract: The past decade has witnessed major advances in our understanding of molecular biology, which led to breakthrough novel therapies, importantly including the B-cell lymphoma-2 (BCL-2) inhibitor venetoclax. Notably, venetoclax-based combinations have improved outcomes, including both remission rates and overall survival, of older patients with acute myeloid leukemia (AML) deemed "unfit" for intensive chemotherapy due to age or comorbidities. This has translated into a rapid and widespread use of venetoclax-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 73 publications
4
62
1
Order By: Relevance
“…Venetoclax has become the most clinically effective BH3-targeting drug approved by the FDA for leukemia treatment and has received FDA approval in several different contexts [136][137][138]. A comprehensive review of venetoclax's use and function has recently been published [139], so it will not be discussed in depth here.…”
Section: Mitochondrial Priming and Bcl-2 Protein Familymentioning
confidence: 99%
“…Venetoclax has become the most clinically effective BH3-targeting drug approved by the FDA for leukemia treatment and has received FDA approval in several different contexts [136][137][138]. A comprehensive review of venetoclax's use and function has recently been published [139], so it will not be discussed in depth here.…”
Section: Mitochondrial Priming and Bcl-2 Protein Familymentioning
confidence: 99%
“…The potent apoptotic effect of BCL-2 inhibition with venetoclax makes TLS a significant risk of treatment [29]. However, incidence of this adverse effect appears to be higher in studies of chronic lymphocytic leukemia (CLL) as compared to the pivotal studies in AML [9]. TLS incidence was noted to be up to 13% with initial phase 1 studies in CLL, which had shorter ramp-up phase and higher starting doses.…”
Section: Lower Intensity Treatmentsmentioning
confidence: 99%
“…Potential risk factors for TLS in AML include bulky disease, leukocytosis, high levels of lactate dehydrogenase, hyperuricemia, and concomitant kidney disease, indicating that uric acidlowering therapy with allopurinol or rasburicase may be important. Caution also may be warranted in AML patients with NPM1 and IDH1/2 mutations, who may also have increased risk of TLS due to an increased sensitivity to venetoclax in these mutation-defined subgroups of AML [9]. Furthermore, Esparza and co-authors reported on 2 patients with venetoclax-induced TLS that had similar genomic profiles (ASXL1, RUNX1, and TET2 mutations), suggesting the potential of this mutational spectrum as a predictor of venetoclax sensitivity [32].…”
Section: Lower Intensity Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high death rate is often a result of mutations that form a difficult -to-treat heterogenous tumor microenvironment [ 1 , 3 ]. With the current therapy, AML patients frequently enter remission, but nearly always relapse and tend to develop resistance to most existing standard-of-care treatments (e.g., induction cytotoxic chemotherapy or venetoclax-based therapy) [ 1 , 4 , 5 , 6 ]. Current targeted therapies are directed towards gene mutations found in AML, such as FMS-like tyrosine kinase 3 (FLT3) [ 7 , 8 , 9 ], KIT [ 10 , 11 ], BCR-ABL [ 12 ], TP53 [ 13 , 14 ], isocitrate dehydrogenase (IDH1 and IDH2) [ 1 , 15 , 16 ], or mixed lineage leukemia (MLL) [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%